Evaluation of Xpert MTB/RIF Assay for Diagnosis of Tuberculosis in Children. (9th February 2018) - Das, Arghya; Anupurba, Shampa; Mishra, Om P; Banerjee, Tuhina; Tripathi, Rajneesh
Abstract: Introduction: Childhood tuberculosis (TB) is now a global priority. With the advent of Xpert MTB/RIF, more TB cases in children are being reported. This study was undertaken to evaluate the performance of Xpert in diagnosis of pulmonary and extra-pulmonary TB in children. Methods: Specimens from 171 suspected TB cases in children aged <15 years were tested with Xpert, culture and smear microscopy in the Department of Microbiology, Institute of Medical Sciences, India. Results: The specimens included 106 gastric aspirates, 51 cerebrospinal fluids, 8 induced sputum and 6 lymph node aspirates. Xpert detected Mycobacterium tuberculosis in 19 cases (14 pulmonary and 5 extra-pulmonary), 7 of which were rifampicin-resistant. Sensitivity, specificity, positive predictive value and negative predictive value of Xpert compared with culture were 88.89, 98.04, 84.21 and 98.68%, respectively. The sensitivity was 100% in children aged 1–5 years and 6–10 years and in gastric aspirates. Conclusion: Xpert is an efficient diagnostic tool in childhood tuberculosis.